2016
DOI: 10.3171/2015.12.peds15496
|View full text |Cite
|
Sign up to set email alerts
|

En bloc resection of a C-1 lateral mass osteosarcoma: technical note

Abstract: Osteosarcoma is an aggressive primary bone tumor. It is currently treated with multimodality therapy including en bloc resection, which has been demonstrated to confer a survival benefit over intralesional resection. The authors present the case of an 8-year-old girl with a C-1 lateral mass osteosarcoma, which was treated with a 4-stage en bloc resection and spinal reconstruction. While technically complex, the feasibility of en bloc resection for spinal osteosarcoma should be explored in the pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Internal fixation is needed to stabilize the cervical spine when >50% of the facet joint is removed, 14 but few studies have reported reconstruction of the lateral mass structure of the cervical spine (Table 2). [15][16][17][18][19][20][21][22][23][24][25][26][27] For primary cervical vertebral tumors, reconstruction of spinal stability after spondylectomy is challenging. Most studies…”
Section: Discussionmentioning
confidence: 99%
“…Internal fixation is needed to stabilize the cervical spine when >50% of the facet joint is removed, 14 but few studies have reported reconstruction of the lateral mass structure of the cervical spine (Table 2). [15][16][17][18][19][20][21][22][23][24][25][26][27] For primary cervical vertebral tumors, reconstruction of spinal stability after spondylectomy is challenging. Most studies…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is actually the main therapeutic tool for this kind of lesions. Particularly, reviewing data from studies of extraspinal osteosarcoma [15], an advantage in terms of local control and long-term survival has been demonstrated by en-block and wide-margin resections, over tumors treated with intralesional resection. Yet, due to the contiguity of vital structures to the spine, not always the total resection can be accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…With new material available as prosthesis, bone implants and bone graft, a complete cure can be offered to patients with huge bone tumours. En block resection of spinal tumours like osteosarcoma that were otherwise devastating is now being carried out successfully [16].…”
Section: Advances In Surgery For Bony Tumoursmentioning
confidence: 99%